Application of Dosege and Interval of Fertilizer on Kale (Brassica oleracea var. Acephala) - Praciska, Intan Okta; Zainudin, Agus; Septia, Erfan Dani (Journal of Tropical Crop Science and Technology, 2021)
The research aimed to explore the impact of vermicompost fertilizer dosage and application timing on kale (Brassica oleracea var. Acephala) varieties. Conducted in Sukoharjo Village from July to September 2020, the study implemented a Randomized Complete Block Design with two factors: vermicompost dosage (D0: NPK 2 g/plant/untreated, D1: 250 g/plant, D2: 500 g/plant, D3: 750 g/plant) and application time (T1: planting, T2: 7 days after planting, T3: 14 days after planting). Analysis revealed no interaction between dosage and application time. Doses of 250 g (D1), 500 g (D2), and 750 g (D3) significantly differed in plant height, leaf number, stem diameter, leaf area, and fresh and dry weights. Notably, the application time at planting (T1), 7 days after planting (T2), and 14 days after planting (T3) significantly affected leaf number. In conclusion, the study found no interaction effect between vermicompost dosage and application time on kale. Doses of 250 g, 500 g, and 750 g exhibited significant differences, impacting plant growth and dry weight. Application times at planting, 7 days after planting, and 14 days after planting significantly influenced leaf number. These findings emphasize the importance of proper dosage and timing for optimizing kale growth with vermicompost fertilizer, contributing to sustainable agricultural practices.